Modeling metabolic homeostasis and nutrient sensing in Drosophila: implications for aging and metabolic diseases - Edward Owusu-Ansah; Norbert Perrimon (The Company of Biologists, 2014)
Over the past decade, numerous reports have underscored the similarities between the metabolism of Drosophila and vertebrates, with the identification of evolutionarily conserved enzymes and analogous organs that regulate carbohydrate and lipid metabolism. It is now well established that the major metabolic, energy-sensing and endocrine signaling networks of vertebrate systems are also conserved in flies. Accordingly, studies in Drosophila are beginning to unravel how perturbed energy balance impinges on lifespan and on the ensuing diseases when energy homeostasis goes awry. Here, we highlight several emerging concepts that are at the nexus between obesity, nutrient sensing, metabolic homeostasis and aging. Specifically, we summarize the endocrine mechanisms that regulate carbohydrate and lipid metabolism, and provide an overview of the neuropeptides that regulate feeding behavior. We further describe the various efforts at modeling the effects of high-fat or -sugar diets in Drosophila and the signaling mechanisms involved in integrating organ function. Finally, we draw attention to some of the cardinal discoveries made with these disease models and how these could spur new research questions in vertebrate systems.